Επαγγελματική εξουθένωση σε νοσηλευτές μονάδων εντατικής θεραπείας - Γαβριήλ, Μαρία (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Background: Nurses’ burnout is one of the main problems of health care during the last decades, especially burnout syndrome in nursing staff of intensive/ critical care units and the risk factors that lead to the syndrome. Aim: This paper work is aiming to investigate the risk factors that are responsible for the burnout syndrome in nursing staff that work in intensive care units. The study will focus on job characteristics that cause burnout syndrome. Method: This is a literature review analysis that uses research papers and articles from electronic data bases such as PubMed, Cinahl, EBSCO and Scholar Google using keywords like intensive care unit, burnout syndrome, risk factors and critical care nurses. Results: The job characteristics of burnout syndrome in nursing staff of the ICU as were recorded in this literature review are the work load, the job demands, job resources, psychological and educational support, working hours and the intense work rhythm, lack of autonomy, lack of staff, lack of nursing staff involvement in decision making, the ergonomic design of ICU, the conflicts with other health care professionals, patients and their families and communication problems. Conclusion: Recording the risk factors burnout syndrome in the intensive care units and by notifying them to nurse managers can influence the administration strategies and actions and turn their attention to the intensive care units for the improvement of the working environment, working relations and working demands and resources.
Keywords: Intensive Care Unit--organization & administration; Critical Care--Nurses' Instruction; Burnout, Professional